A review of burnout in college English teachers in China - Zheng, Yurong (Frontiers in Psychology, 2022)
College English teachers’ job burnout has become prominent in the field of education. This review research on burnout of college English language teachers in China from 2006–2021 within the China National Knowledge Infrastructure (CNKI) database. The reviewed studies demonstrated medium- or high-level symptoms of burnout in a relatively high percentage of college English teachers in China. Individual variables, such as educational background, teaching workload, professional title, years of teaching experience, and university level and category were associated with burnout rates. The job characteristics related to a college English teacher’s job burnout include teaching-related role overload, scientific research stress induced by promotion, limited job autonomy, a stern hierarchical organizational system, and opaque operating rules. Possible ways to reduce burnout across societal, school and individual levels, along with practical implications and limitations are discussed.